Adsorption of nitrate from interflow by the Mg/Fe calcined layered double hydroxides - Chu, Liquan (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
Nitrate loss in interflow caused serious nitrate pollution of neighboring water bodies in the purple soil region of China's Sichuan Province. In this study, Mg/Fe(Al)-calcined layered double hydroxides (Mg/Fe(Al)-CLDHs) with varied Mg/Fe(Al) ratios were synthesized for nitrate removal from interflow, and 3:1 Mg/Fe CLDH exhibited the best adsorption performance. The effects of initial pH, adsorbent dosage and co-existing anions on the adsorption performance were investigated by batch experiments. The best-fitting kinetic and isothermal models for nitrate adsorption were the pseudo-second-order model and Freundlich model, respectively, indicating that the adsorption process was a physical-chemical multilayer process. The maximum adsorption capacity of nitrate was 73.36 mg/g, which was higher than that of many other commonly used adsorbents. The adsorbents were characterized by X-ray diffraction (XRD), Fourier transform infrared (FT-IR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), transmission electron microscope (TEM) and Brunauer-Emmett-Teller (BET) techniques, and the XRD and FT-IR results revealed that the adsorption mechanism involved original layered structure reconstruction and ion-exchange interaction. Under the coexistence of SO42- and Cl-, 75.63% nitrate in interflow could be removed after 6 h of adsorption. Overall, the synthesized Mg/Fe CLDH is an effective and low-cost nitrate adsorbent for in-situ nitrate removal